(untitled) - Konopka, Dave (Hoboken, N.J., 2008)
Windows Sidebar is a new feature of the Windows Vista operating system that allows desktop opening of mini-applications called gadgets. Web developer/writer Konopka explains that, like Web pages, gadgets are composed of HTML and JavaScript; but unlike most Web pages, they can also interact with other Vista features and other computer programs. He covers downloading and installing gadgets to customizing and updating them. "Extra" tips provide more advanced information on working with gadgets. The companion Web site includes a basic interactive gadget and resources for creating the book's examples. Annotation ©2008 Book News, Inc., Portland, OR (booknews.com)
Keywords: Microsoft Windows (Operating System),Hệ điều hành Windows